A broad spectrum of genomic changes in latinamerican patients with EXT1/EXT2-CDG - Delgado, M. A. (2014)
Multiple osteochondromatosis (MO), or EXT1/EXT2-CDG, is an autosomal dominant O-linked glycosylation disorder characterized by the formation of multiple cartilage-capped tumors (osteochondromas). In contrast, solitary osteochondroma (SO) is a non-hereditary condition. EXT1 and EXT2, are tumor suppressor genes that encode glycosyltransferases involved in heparan sulfate elongation. We present the clinical and molecular analysis of 33 unrelated Latin American patients (27 MO and 6 SO). Sixty-three percent of all MO cases presented severe phenotype and two malignant transformations to chondrosarcoma (7%). We found the mutant allele in 78% of MO patients. Ten mutations were novel. The disease-causing mutations remained unknown in 22% of the MO patients and in all SO patients. No second mutational hit was detected in the DNA of the secondary chondrosarcoma from a patient who carried a nonsense EXT1 mutation. Neither EXT1 nor EXT2 protein could be detected in this sample. This is the first Latin American research program on EXT1/EXT2-CDG.